1.) To solve the system of equations:
8x - 3y = -22
y = 10 + 4x
We can substitute the second equation into the first equation:
8x - 3(10 + 4x) = -22
Simplifying this equation, we get:
8x - 30 - 12x = -22
-4x - 30 = -22
-4x = 8
x = -2
Substituting this value of x back into the second equation, we find:
y = 10 + 4(-2)
y = 10 - 8
y = 2
Therefore, the solution to the system of equations is (-2, 2).
2.) To solve the system of equations:
5x + 2y = 14
x - 6y = 22
We can solve this system of equations using the method of substitution or elimination.
Let's use the method of substitution for this problem.
Solving the second equation for x, we get:
x = 22 + 6y
Substituting this expression for x into the first equation, we have:
5(22 + 6y) + 2y = 14
110 + 30y + 2y = 14
110 + 32y = 14
32y = -96
y = -3
Substituting this value of y back into the second equation, we find:
x - 6(-3) = 22
x + 18 = 22
x = 4
Therefore, the solution to the system of equations is (4, -3).
3.) To solve the system of equations:
-9x + y = 12
2x + 4y = -28
We can solve this system of equations using the method of substitutions or elimination.
Let's use the method of elimination for this problem.
We can multiply the first equation by 4, and the second equation by 9, to create coefficients that will cancel each other out.
Multiplying the first equation by 4, we get:
-36x + 4y = 48
Multiplying the second equation by 9, we get:
18x + 36y = -252
Adding these two equations together, the x terms cancel out:
-36x + 4y + 18x + 36y = 48 - 252
40y = -204
y = -5.1
Substituting this value of y back into the first equation, we find:
-9x + (-5.1) = 12
-9x - 5.1 = 12
-9x = 17.1
x = -1.9
Therefore, the solution to the system of equations is (-1.9, -5.1).
4.) To determine the number of solutions for the system of equations:
6x + 2y = -18
3x + y = 24
We can solve this system of equations using the method of substitution or elimination.
Let's use the method of elimination for this problem.
We can multiply the second equation by 2, to create coefficients that will cancel each other out.
Multiplying the second equation by 2, we get:
6x + 2y = -18
6x + 2y = 48
Subtracting these two equations, we get:
0 = 66
Since 0 = 66 is a contradiction, we can conclude that the system of equations has no solutions.
Alternatively, we can observe that the coefficients of x and y are different in the two equations. This implies that the lines represented by the equations are not parallel or coincide, and therefore there is no solution to the system of equations.
Solve the system of equations.
8x−3y= −22
y=10+4x (1 point)
( , )
_____________________________________2.)Solve the system of equations.
5x+2y=14
x−6y=22 (1 point)
( , )
___________________________________3.) Solve the system of equations.
–9x+y=12
2x+4y= −28 (1 point)
( , )
___________________________________4.) How many solutions does the system of equations have?
6x+2y=−18
3x+y=24 (1 point)
___________________________________
3 answers
Question 1 is wrong.
I apologize for the mistake. Let's solve the system of equations correctly:
1) Solving the system of equations:
8x - 3y = -22
y = 10 + 4x
We can substitute the expression for y from the second equation into the first equation:
8x - 3(10 + 4x) = -22
8x - 30 - 12x = -22
-4x - 30 = -22
-4x = -22 + 30
-4x = 8
x = -2
Substitute this value of x back into the second equation to find y:
y = 10 + 4(-2)
y = 10 - 8
y = 2
Therefore, the solution to the system of equations is (-2, 2).
Note: I apologize for the incorrect solution provided initially. Thank you for bringing it to my attention.
1) Solving the system of equations:
8x - 3y = -22
y = 10 + 4x
We can substitute the expression for y from the second equation into the first equation:
8x - 3(10 + 4x) = -22
8x - 30 - 12x = -22
-4x - 30 = -22
-4x = -22 + 30
-4x = 8
x = -2
Substitute this value of x back into the second equation to find y:
y = 10 + 4(-2)
y = 10 - 8
y = 2
Therefore, the solution to the system of equations is (-2, 2).
Note: I apologize for the incorrect solution provided initially. Thank you for bringing it to my attention.